Insulin resistance and cardiovascular outcomes in the ORIGIN trial. Issue 3 (8th October 2017) - Gerstein, Hertzel C.; Ferrannini, Ele; Riddle, Matthew C.; Yusuf, Salim; ,
Abstract : Aims: In the Outcome Reduction with an Initial Glargine Intervention (ORIGIN) trial (Clinicaltrials.gov : NCT000069784), titrated doses of basal insulin glargine targeting fasting normoglycaemia had a neutral effect on cardiovascular outcomes. The dose of insulin required to achieve normoglycaemia provides a unique measurement of each individual's resistance to insulin's action, and was therefore used to examine the link between insulin resistance and cardiovascular outcomes. Materials and Methods: Self‐titration of insulin doses targeting a fasting plasma glucose ≤5.3 mmoL/L (95 mg/dL) was promoted at every visit and cardiovascular and other serious health outcomes were ascertained. All analyses were restricted to participants allocated to insulin glargine, who added it to lifestyle or 1 glucose‐lowering oral agent at randomization. Normoglycaemia was defined as a fasting plasma glucose <5.6 mmol/L and HbA1c <6% at the 2‐year visit. The median of the natural logarithm of insulin doses (expressed per kg of fat‐free mass), recorded at every visit from randomization until either the penultimate visit or the first occurrence of a cardiovascular outcome, was analysed. Results: Higher median insulin doses did not reflect incident cardiovascular events overall or in the subset that achieved normoglycaemia. When the dose taken before a cardiovascular event or the penultimate visit was analysed, the adjusted hazard of the composite of cardiovascular death, myocardial infarction or stroke was 0.94 (95% CI 0.88, 1.00) per unit higher dose overall, and 0.91 (95% CI 0.81, 1.01) in the normoglycaemic subset. Conclusions: Insulin resistance may not promote cardiovascular outcomes in individuals with dysglycaemia.